A Review of Safety Features of Small Modular Reactor (SMR): Malaysian Nuclear Program Perspective - Md Kasmani, Rafiziana; Khattak, Muhammad Adil; Mahadi, Muhammad Zulhelmi; Miftah, Nurfarahin; Hor Yen, Tiu; Jamaluddin, Khairulnadzmi; Noorizab, Muhammad Faiz Farhan; Borhana Omran, Abdoulhdi Amhmad; Ahmed, Ali Najah (Journal of Advanced Research in Applied Mechanics, 2020)
Mobile nuclear reactor is a new technology which is still under development in most of the countries. Based on the proposed design idea, definitely there are some possible constraints that need to be considered during its design process. Basically, constraints are the rules or limitations through which design is conceived and created. Safety assessment method used in the project is based on the method proposed by Department of Safety and Health, DOSH. The key to safety is to create multiple independent and redundant layers of defense to compensate for potential human and mechanical failures so that no single layer is exclusively relied upon. Defence?in?depth is one of the strategies that will be implemented in designing a reactor. It includes the use of access controls, physical barriers, redundant and diverse key safety functions, and emergency response measures. Defence?in?depth can be grouped into three levels. Level one is the prevention of occurrence of abnormal state, level two is prevention of development of an abnormal state to an accident and level three is protection of abnormal release of radioactive materials into environment. According to IAEA-TECDOC-626, the concepts of passive and active safety systems are defined and discussed. A passive safety system is defined as: either a system which is composed entirely of passive components and structures or a system which uses active components in a very limited way to initiate subsequent passive operation.